The effect of real earnings management on earnings persistence and informativeness before and during COVID-19 - Le Thi Bao Nhu; Tran Thi Hong Diem; Yen Thi Tran; Trang Cam Hoang (My University, 2023)
The effect of real earnings management on earnings persistence and informativeness before and during COVID-19
Keywords: Earnings management; Earnings persistence; COVID-19